Cervicogenic Headache and Physiotherapy: A Systematic Review of Treatment Modalities - Manali Sanket Chitlange; Pallavi Harjpal (Journal of Clinical and Diagnostic Research, 2025)
Introduction: A common, but frequently misdiagnosed, condition known as Cervicogenic Headache (CGH) is characterised by pain radiating from the cervical spine to the head. CGH can significantly impact quality of life, leading to disability and reduced productivity. It also provides information regarding the nature of CGH. External pressure on the neck and movements of the neck, such as extension, rotation, or lateral flexion, may trigger the headache, which may then spread to the ipsilateral orbito-frontal-temporal or facial regions. Pain is referred from cervical structures due to the convergence of sensory pathways in the trigeminal-cervical complex. Dysfunction or irritation of cervical joints, muscles, or nerves can contribute to CGH symptoms. Physical therapy targets the cervical spine, which is often involved in CGHs. Techniques aim to improve joint function, reduce muscle tension, and enhance cervical stability. Therapy helps to restore normal cervical function, improve posture, and enhance overall quality of life. Patients also learn about self-management strategies, ergonomic adjustments, and lifestyle modifications to prevent exacerbation. This structured background provides a comprehensive overview of CGHs and the role of physical therapy in their management and effectiveness. Aim: This article aims to provide a thorough overview of CGHs, covering a range of physical therapy treatments. Materials and Methods: In the present systematic review, a literature search was conducted to find pertinent studies and reviews on cervicogenic headache, using the PubMed database. Key search terms included “cervicogenic headache” and “physiotherapy.” Only English-language research published between 2005 and 2024 were included in the search. The platform “RAYYAN” was used for the screening of articles and provides information regarding duplicate and unresolved articles. Results: In the identification phase, a search of databases and registers yielded 40 potentially relevant records. During the screening process, two duplicates were removed, leaving 38 records for further evaluation. Of these, 21 were excluded for reasons such as irrelevance to the research question or differing study types. The remaining 17 records underwent assessment based on predefined inclusion and exclusion criteria. Ultimately, 11 studies met the eligibility requirements and were included in the systematic review. Articles with titles related to CGH and physiotherapy were included. The subjects were children, as well as male and female adults. A Clinical Trial (CT) and Randomised Controlled Trial (RCT) study design including 13 various interventions published from 2005 to 2024 were selected. All studies were written in English and had free full-text availability. Conclusion: Given the complexity of cervicogenic headache, multiple modalities must be used in diagnosis and treatment. To improve patient outcomes and optimise therapeutic techniques, further research is required.